The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/cts.13033
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor predicts an unfavorable outcome after transarterial chemoembolization for hepatic malignancies

Abstract: Transarterial chemoembolization (TACE) is a therapeutic option for patients with intermediatestage hepatocellular carcinoma (HCC) or metastatic liver cancers. Identifying those patients who particularly benefit from TACE remains challenging. Macrophage migration inhibitory factor (MIF) represents is an inflammatory protein described in liver cancer patients, but no data on its prognostic relevance in TACE patients exist. Here, we evaluate MIF serum concentrations as a Accepted ArticleThis article is protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Our data are of clinical relevance, as we provide insights into how MIF and its cognate receptor CD74 drive hepatocarcinogenesis in vivo and complement the human studies that have previously indicated a prognostic relevance of MIF and CD74 expression in HCC patients (Hira et al, 2005;Wirtz et al, 2021). Nevertheless, further animal studies are needed to evaluate the effects of an anti-CD74 directed therapy during HCC growth, for example, in models of orthotopic HCC transplant in murine livers previously treated with fibrogenic agents (Liu et al, 2020;Reiberger et al, 2015).…”
Section: Macrophage Migration Inhibitory Factor Promotes Erk Phosphorylation In Hepatoma Cells In a Cd74-dependent Mannersupporting
confidence: 56%
“…Our data are of clinical relevance, as we provide insights into how MIF and its cognate receptor CD74 drive hepatocarcinogenesis in vivo and complement the human studies that have previously indicated a prognostic relevance of MIF and CD74 expression in HCC patients (Hira et al, 2005;Wirtz et al, 2021). Nevertheless, further animal studies are needed to evaluate the effects of an anti-CD74 directed therapy during HCC growth, for example, in models of orthotopic HCC transplant in murine livers previously treated with fibrogenic agents (Liu et al, 2020;Reiberger et al, 2015).…”
Section: Macrophage Migration Inhibitory Factor Promotes Erk Phosphorylation In Hepatoma Cells In a Cd74-dependent Mannersupporting
confidence: 56%
“…In other studies related to HCC, the expression of MIF was higher in HCC tissues than in healthy or adjacent non-tumor liver tissues ( 17 , 22 ). MIF was measurable in sera from patients with HCC, and the level was associated with hepatic tumor size and outcome of patients receiving transcatheter arterial chemo embolization ( 23 ). One of the limitations of the present study is the lack of analysis between serum MIF levels and expression levels of ILT2 on CD56 dim NK cells due to the scarcity of serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, MIF was found to synergistically induce the growth of HCC cells in the research of HCC, 20 which makes it possible to inhibit the growth of HCC by regulating the expression and function of MIF. Given that MIF is an indicator of early diagnosis, a potential therapeutic target, and a biomarker for HCC progression and patient prognosis, 21,22 reliably mapping the levels of MIF is thus greatly important.…”
mentioning
confidence: 99%